Pregnancy outcome after diagnosis of oligohydramnios at term - Chate, Preshit; Khatri, Meena; Hariharan, C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: To study the perinatal outcome in oligohydramnios (AFI < 5) at term & find out incidence of relation of maternal high risk factors. Methods: A Prospective case control study consists of an analysis of pregnancy outcome in 50 cases with diagnosis of oligohydramnios by ultrasound after 37 completed weeks of gestation compared with 50 controls with no oligohydramnios. Results: The selected outcomes showed significant variations in both groups. There were increased chances of FHR decelerations, Thick meconium, low Apgar score at 5 min. ,birth weight <2.5 kg, admission to NICU, congenital anomalies & neonatal mortality(statistically not significant). Conclusions: An amniotic fluid index of < 5 cm detected after 37 completed weeks of gestation is an indicator of poor perinatal outcome. Determination of AFI can be used as an adjunct to other fetal surveillance methods. It helps to identify those infants at risk of poor perinatal outcome.